Intrusion Detection in Hospital Automation using Internet of Things (IoT): An Overview. - REDDY, SERESANE V. KRISHNA; MURTHY, JAYANTHI K. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Development in the Healthcare sector plays a vital role in everyone's life. In the current trend, there is an increasing demand for data maintenance and security in this sector. Also, there is an increase in the requirement for storage space for maintaining the patient's information. It indeed aids in the quick review of the patient's health anywhere and anytime by the doctors. Here comes the role of the Internet of Things (IoT). While there is an increased utilization of the IoT devices, care should also be taken to provide security to the data. Disregardless leads to attacks like Mirai botnet. Hence, in the IoT networks, there is an increased threat to security and privacy of the information in any field or sector, which forms a significant issue in the real world. So, to mitigate IoT related security attacks, there is a need to design an Intrusion detection system which can overcome the threats in IoT systems. Intrusion detection systems are used to detect unusual activity, identify the unauthorized and to enable a response to that violation. As the records or data of the hospitals is increasing rapidly, the storage of data should also be cost-efficient, convenient and must also provide fast communication. But the potential threats to that information made Intrusion Detection System (IDS) a necessity. This survey paper presents a comprehensive survey if the IDSs, that are specifically designed for IoT along with the methods, mechanisms and placement strategy used. Along with the previous studies at the end a reliable and robust IDS architecture will be proposed with its capabilities mentioned.